Breast Reconstruction Free Flap Failure: Does Platelet Count Matter?. Issue 5 (November 2022) - Kalmar, Christopher L.; Drolet, Brian C.; Kassis, Salam; Thayer, Wesley P.; Higdon, Kent K.; Perdikis, Galen
Abstract : Background: Microvascular free tissue transfer is an increasingly popular modality for autologous tissue breast reconstruction. However, flap failure remains an ominous risk that continues to plague surgeons and patients even in the setting of meticulous surgical technique and monitoring. Venous and arterial thromboses are the leading causes of free flap failure. The purpose of this study was to determine whether thrombocytosis is associated with breast free flap failure. Methods: A retrospective study was conducted of breast reconstruction with free flaps in North America between 2015 and 2020 using the National Surgical Quality Improvement Program database. Patient comorbidities and preoperative laboratory tests were used to determine risk factors for free flap failure. Results: During the study interval, 7522 female patients underwent breast reconstruction with free flaps, and flap failure occurred in 2.7% patients (n = 203). In multivariate regression analysis, breast free flap failure was significantly higher in patients smoking cigarettes within the past year ( P = 0.030; AOR, 1.7) and dyspnea on moderate exertion or at rest ( P = 0.025; AOR, 2.6). Furthermore, each 50 K/mcL elevation in platelet count was independently associated with an increased odds of flap failure ( P < 0.001; AOR, 1.2). Patients experienced significantly higher rates of flap failure with platelet counts greater than 250 K/mcL ( P = 0.004), which remained significant through progressively increasing thresholds up to 450 K/mcL. Conclusions: Platelet count greater than 250 K/mcL is associated with progressively increasing risk of free flap failure in breast reconstruction. Future studies of personalized patient anticoagulation protocols based on hemostatic metrics may improve free flap survival after autologous tissue breast reconstruction.